PREPARATION AND PROPERTIES OF A PROTEIN (R ANTIGEN) OCCURRING IN STREPTOCOCCI OF GROUP A, TYPE 28 AND IN CERTAIN STREPTOCOCCI OF OTHER SEROLOGICAL GROUPS - Lancefield, Rebecca C. (The Rockefeller University Press, 1952)
A group A, type 28 protein antigen, resistant to tryptic digestion and previously considered to be a type-specific substance, was purified and its chemical and immunological properties studied. This protein lacks the characteristic properties of a type-specific M antigen since it is apparently unrelated to virulence and does not induce the formation of protective antibodies although precipitins are readily produced. It is designated the R antigen. The R antigen in addition to occurring in "type 28" group A strains also occurs in some strains of streptococci of other serological groups. Protective antibodies, distinct from precipitins for the R antigen, are present in "type 28" antibacterial sera. The antigens responsible for protection have not been identified, and it is possible that several different types may be included among strains designated as type 28 on the basis of the R antigen. The purified R antigen is phosphorus-free and has a sulphur content of 1.04 per cent. In the ultraviolet a maximum absorption was obtained at a wave length of 280 mµ and a minimum at 254 mµ. Electrophoretically the R antigen was found to be 95 per cent homogeneous at most pH values, but at pH 4.6 the main peak separated into two peaks of approximately equal areas, both containing serologically active material. The interpretation of this finding is at present uncertain. The isoelectric pH was at 4.5 in sodium acetate buffer of 0.1 ionic strength. The purified R antigen sedimented in the ultracentrifuge as a single boundary.